The diversity of emergent aquatic plant species in ponds at UiTM Kuala Pilah, Cawangan Negeri Sembilan / Madihah Abd Rahim - Abd Rahim, Madihah (Faculty of Applied Sciences, 2017)
The variety of life forms within a given species, ecosystem, biome or planet is known as biodiversity. Biodiversity can also be referred as species diversity and species richness. Understanding the drivers of biodiversity requires an understanding of intertwined biotic and abiotic factors, including climate patterns over the earth. The aim of this study is to determine the diversity patterns of emergent aquatic plants. Generally, types of aquatic plants play a significant role in the ecology of large numbers of freshwater ecosystems worldwide. There are total of 145 individuals which consist of four families of emergent aquatic plants that represent 7 genera. Each species are preserved and identified as the sample collected. The family of Cyperaceae and Onagraceae has five and one genus respectively while Juncaceae and Poaceae consist only two genera. Where, the highest family collected was Cyperaceae which have 50 individuals, while the lowest family collected was Onagraceae with 23 individuals. The genera Phalaris is the most abundant which has 31 individuals followed by Scirpus with 27 individuals, Juncus with 25 individuals, Ludwigia with 23 individuals, Phragmites with 16 individuals and Carex with 14 individuals. The least genera collected were Eleocharis which only has 9 individuals. The diversity pattern of species in ponds at UiTM Kuala Pilah, Negeri Sembilan is stable with Shannon's Diversity index is H= 1. 1, while Evenness Index is E= 1 and the Richness Index is D=0.42. From this study, there is no eutrophication occurred as the calculated Evenness index is 1.